2013
DOI: 10.1158/1541-7786.mcr-12-0718
|View full text |Cite
|
Sign up to set email alerts
|

ERK-Dependent Downregulation of Skp2 Reduces Myc Activity with HGF, Leading to Inhibition of Cell Proliferation through a Decrease in Id1 Expression

Abstract: Hepatocyte growth factor (HGF) has an inhibitory effect on human HepG2 hepatoma cell proliferation. Previously, it was shown that HGF treatment downregulated Id1 and upregulated p16 INK4a in an ERK-dependent manner, leading to the inhibition of cellular proliferation. Here, new insight suggests that Skp2, an SCF complex component and potential prognosticator in cancer, is downregulated by injection of HGF into established HepG2 xenograft tumors. The downregulation was evident at both the mRNA and protein level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
(70 reference statements)
1
12
0
Order By: Relevance
“… 3 In this regard, we found that exogenous interleukin-6 (IL-6) or insulin-like growth-factor-1 (IGF-1) or hepatocyte growth-factor (HGF) significantly reduced miR-125b-5p expression in all MM cell lines except U266 cells ( Figure 6a ), which express L-Myc instead of c-Myc. Since c-Myc suppresses miR-125b transcription 39 , 40 and is upregulated by IL-6, IGF-1 and HGF, 40 , 41 , 42 we investigated whether these factors downregulate miR-125b in MM cells through c-Myc induction. Specifically, we treated c-Myc-expressing SK-MM-1 and c-Myc-defective U266 cells with the 10058-F4 small molecule inhibitor of Myc–Max heterodimerization 38 and with the JQ1 BET-bromodomain inhibitor, which is reported to inhibit c-Myc transcription.…”
Section: Resultsmentioning
confidence: 99%
“… 3 In this regard, we found that exogenous interleukin-6 (IL-6) or insulin-like growth-factor-1 (IGF-1) or hepatocyte growth-factor (HGF) significantly reduced miR-125b-5p expression in all MM cell lines except U266 cells ( Figure 6a ), which express L-Myc instead of c-Myc. Since c-Myc suppresses miR-125b transcription 39 , 40 and is upregulated by IL-6, IGF-1 and HGF, 40 , 41 , 42 we investigated whether these factors downregulate miR-125b in MM cells through c-Myc induction. Specifically, we treated c-Myc-expressing SK-MM-1 and c-Myc-defective U266 cells with the 10058-F4 small molecule inhibitor of Myc–Max heterodimerization 38 and with the JQ1 BET-bromodomain inhibitor, which is reported to inhibit c-Myc transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking predicts the best interaction of proteinligand complexes virtually and determines the appropriate orientation of the inhibitor when bound to a protein [36]. The crystal structure of p53 tumor suppressor protein PDB_ID: 1TSR_B with resolution 2.20Å; crystal structure Hepatocytes Growth Factor PDB_ID: 3HN4_A with resolution of 2.60Å and the crystal structure of TREM1 PDB_ID: 1Q8M_A with resolution of 2.60Å are retrieved from protein data bank.…”
Section: Docking Studies Of Mct With Hcc Inducing Factorsmentioning
confidence: 99%
“…Equal amounts of protein in the precleared cell extracts (30 ÎŒg of total protein) were resolved by sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS–PAGE) on 10% gel after heat denaturation. Immunoblotting was carried out following standard procedures as previously described (Li et al, ). Antibodies used for immunoblotting were as follows: anti‐CYP2e1 antibody (AB1252) from Merck Millipore, anti‐ÎČ‐actin antibody from Sigma‐Aldrich, and anti‐Bmal1 antibody (ab93806) and anti‐Per2 antibody (ab180655) from Abcam.…”
Section: Methodsmentioning
confidence: 99%